Characterising the difference in electrophysiological substrate and outcomes between heart failure and non-heart failure patients with persistent atrial fibrillation. Issue 3 (20th January 2017) - Haldar, Shouvik K; Jones, David G; Khan, Habib; Panikker, Sandeep; Jarman, Julian W E; Butcher, Charlie; Lim, Eric; Wynn, Gareth; Gupta, Dhiraj; Hussain, Wajid; Markides, Vias; Wong, Tom
Abstract: Aims: Characterizing the differences in substrate and clinical outcome between heart failure (HF) and non-heart failure (non-HF) patients undergoing persistent atrial fibrillation (AF) ablation. Methods and results: Using complex fractionated electrograms (CFE) as a surrogate marker of substrate complexity, we compared the bi-atrial substrate in patients with persistent AF with and without HF, at baseline and after ablation, to determine its impact on clinical outcome. In this retrospective analysis of two prospective studies, 60 patients underwent de-novo step-wise left atrial (LA) ablation, 30 with normal left ventricular ejection fraction (LVEF) ≥ 50% (non-HF group) and 30 with LVEF ≤ 35% (HF group). Multiple high-density bi-atrial CFE maps were acquired along with AF cycle length (AFCL) at each procedural stage. Change in bi-atrial CFE areas, AFCL and outcome data were then compared. In the non-HF group, higher CFE-areas were found at baseline and at each step of the procedure in the LA. In both LA and the right atrium (RA), baseline and final CFE area were also higher in the non-HF group. Single procedure, arrhythmia-free survival at 1 year was higher in the HF group compared with the non-HF group (72% vs. 43%, log rank P  = 0.04). Final total bi-atrial CFE area was an independent predictor of arrhythmia recurrence. Conclusions: CFE represents an important surrogate marker of atrial substrate complexity. The atrial substrate in persistent AF differs between HF and non-HF with the latter representing a more complex 'primary' bi-atrial myopathy. LA focussed ablation results in more extensive substrate modification in HF and better clinical outcomes as compared with non-HF.